Prognostic Value of Hyperechoic Echo Halo in cN0 Papillary Thyroid Microcarcinoma and Its Correlation with Age and Gender. (28th February 2020) - Zheng, Xiaojuan; Jiang, Yunwen; Zhao, Chenyin; Peng, Minxia; Qian, Liyong
Abstract : Purpose . To investigate the pathology and prognostic value of hyperechoic echo halo in cN0 papillary thyroid microcarcinoma (PTMC) and the relationship between age, gender, and the formation of abnormal hyperechoic echo halo and cervical lymph node metastasis. Data of 97 patients who underwent surgical treatment for the first time for single PTMC between April 2016 and March 2017 were analyzed retrospectively. The boundary status of the PTMC was determined preoperatively. Grayscale values of the nodular center, hyperechoic echo halo, and normal thyroid tissue were acquired with Adobe Photoshop CS6 software. The histopathology of the boundary and status of the cervical lymph node metastasis were analyzed. Formation of abnormal hyperechoic halo and cervical lymph node metastasis in relation to age and gender were explored. The abnormal hyperechoic halo mainly represents cancer cell infiltration with reactive hyperplasia of inflammatory cells and fibrous tissue. In the hyperechoic halo group, the grayscale values for the nodular center, hyperechoic echo halo, and normal thyroid tissue were 1552.6 ± 578.6, 5792.0 ± 747.6, and 3582.7 ± 759.0, respectively (P < 0.05 ). The cervical lymph node metastasis rate was significantly lower in patients with hyperechoic halo (15.0%) than in those without (41.6%; P < 0.05 ) and significantly higher in those aged <45 years (53.3%) than in those aged ≥45 years (28.4%; P < 0.05 ). There were no significant correlations between gender and cervical lymph node metastasis or between age, gender, and hyperechoic halo formation (P > 0.05 ). cN0 PTMC patients with abnormal hyperechoic halo and age >45 years have a significantly reduced risk of cervical lymph node metastasis and relatively good prognosis.